Pengaruh Bahan Stek dan Bentuk Rootone terhadap Pertumbuhan Mawar - Erita Hayati; Mardhiah Hayati; Heramika Yulis (Jurnal Agrista, 2009)
Effect of Cutting and Forms Rootone F on the Growth of the Roses (Rosa sp)ABSTRACT. This study aims to determine the effect of cutting and way of giving proper rootone F and the presence or absence of interaction between the two factors under study on the growth of cutting roses. The research was conducted in the Village of Blang Cut, District Leung Bata, Banda Aceh, the ongoing since August – October 2006. This research used randomized block design factorial pattern of 3x4 with 3 replications. There are two factors studied were the first factor is the cutting material (S) which consists of 3 levels: the base of cutting (S1), cutting the middle (S2) and cutting the tip (S3), the second factor is the form rootone F consists of 4 levels: Control (R0), from a paste (R1), the form of flour (R2) and forms a solution of (R3). Observed in this study is to shoot length, number of shoot, number of compound leaves per shoot, number of root and root length. The result showed that the materials have strong cuttings of shoot number of age 60 days after transplanting (DAT), the number of compound leaves per shoot, number of roots and root length HST age 80, the best result encountered in cutting edge treatment material (S3) Treatment rootone F shows that the effect is very significant effect on the number of shoots age 60 DAT, the number of compound leaves, number of root and root length HST age 80, the best result encountered in the treatment of flour (R2). There is significant interaction on the number of compound leaves per shoot, root length and number of root age 80 DAT, the best interaction was obtained at S3R2 combination treatment.